BLACK HULLED BARLEY MARKETING PRICES vs. WHITE in SOUTH-EAST ANATOLIA - Özberk, Fethiye; Özberk, İrfan; Ayhan, Huseyin; Bayhan, Merve; İpeksever, Fahriye (Journal of Agricultural Sciences (Belgrade), 2020)
This study aimed to assess the presence of various ratios of black and white hulled grains in barley grain lots and impacts on marketing price. The study was carried out in Sanlıurfa commodity market in the autumn of 2005 in Sanlıurfa and Diyarbakir in 2015 and Sanliurfa, Adıyaman and Gaziantep local commodity markets in 2017. The seven barley grain samples were prepared [ 100% White (W), 10% Black(B)+90% White(W), 20%B+80%W, 30%B+70%W, 40%B+60%W, 50%B+50%W and 100% Black] and presented to randomly selected four grain purchasers in all commodity markets and marketing price offers were scored. Some of grain quality traits such as protein ratio (%), hectoliter weights (kg), 1000 kernel weights (g) and grain plumpness (%) were also scored in the final year. Increasing ratios of black-hulled barley (BHB) reduced marketing price gradually in 2005. A 0.180 US$ kg-1 was offered to 100% White-Hulled Barley (WHB) whereas only 0.168 US$ kg-1 for 100% BHB in Sanlıurfa. In 2015, these were 0.337 US$ kg-1 for white and 0.365 US$ kg-1 for black in Sanliurfa and 0.334 US$ kg-1 for white and 0.352 US$ kg-1 for black in Diyarbakir. In 2017, WHB received 0.292 US$ kg-1 marketing price offer and BHB 0.274 US$ kg-1 in Adıyaman whereas in both Sanliurfa and Gaziantep these turned out to be in favor of BHB and it received 0.37 US$ kg-1 and 0.321 US$ kg-1 marketing price offers respectively. Those of WHB marketing prices were 0.325 US$ kg-1 and 0.315 US$ kg-1 in both locations respectively.  Regression equations obtained from 2017 data could be used for price estimates reliably with high coefficients of determinations. It was concluded that except Adıyaman, barley marketing prices traditionally in favor of white hulled turned out to be in favor of black type in a decade in south-east Anatolia. But the less return and yielding ability of BHB may not be sufficient for its survival in long term